2021
DOI: 10.1152/ajpgi.00066.2021
|View full text |Cite
|
Sign up to set email alerts
|

Visceral myopathy: clinical syndromes, genetics, pathophysiology, and fall of the cytoskeleton

Abstract: Visceral smooth muscle is a crucial component of the walls of hollow organs like the gut, bladder, and uterus. This specialized smooth muscle has unique properties that distinguish it from other muscle types and that facilitate robust dilation and contraction. Visceral myopathies are diseases where severe visceral smooth muscle dysfunction prevents efficient movement of air and nutrients though the bowel, impairs bladder emptying, and affects normal uterine contraction and relaxation, particularly during pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 98 publications
(102 reference statements)
0
36
0
Order By: Relevance
“…Recently, it was reported that the ACTG2 gene, which encodes gSMA, is mutated in 30% of children with CIPO who have a worse outcomes and severe GI dysmotility often associated with the presence of megacystis (Hashmi et al, 2021;Matera et al, 2016). In pediatric patients with CIPO, prenatal signs are detected only in about 20% of cases, mainly the presence of megacystis, although 50-70% of infants show clinical signs in the first month after birth (Di Nardo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that the ACTG2 gene, which encodes gSMA, is mutated in 30% of children with CIPO who have a worse outcomes and severe GI dysmotility often associated with the presence of megacystis (Hashmi et al, 2021;Matera et al, 2016). In pediatric patients with CIPO, prenatal signs are detected only in about 20% of cases, mainly the presence of megacystis, although 50-70% of infants show clinical signs in the first month after birth (Di Nardo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric Chronic Intestinal Pseudo-Obstruction (CIPO) syndrome is the most severe functional gastrointestinal disorder (high morbidity and mortality rates), but lacks standardized diagnostic and therapeutic approaches (Thapar et al, 2018). Recently, it was reported that the ACTG2 gene, which encodes ΨSMA, is mutated in 30% of children with CIPO who have a worse outcomes and severe GI dysmotility often associated with the presence of megacystis (Hashmi et al, 2021; Matera et al, 2016). In pediatric patients with CIPO, prenatal signs are detected only in about 20% of cases, mainly the presence of megacystis, although 50–70% of infants show clinical signs in the first month after birth (Di Nardo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The most severe inherited disorders of smooth muscle cell function, referred to as multisystemic smooth muscle dysfunction syndrome (MSMDS) or megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS), manifest in infancy with life-threatening defects in GI motility and are associated with mutations in the genes coding for components of the contractile machinery, including myosin light chain kinase ( MYLK ), SMA ( ACTA2 ), and myosin heavy chain-11 ( MYH11 ) ( Moreno et al, 2016 ; Gamboa and Sood, 2019 ; Hashmi et al, 2021 ). Defects in pupil constriction have been reported in patients with MSMDS/MMIHS, consistent with contractile defects in iris smooth muscle ( Moller et al, 2012 ; Roulez et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that DSS administration is used to model IBD in zebrafish and other animal models (Chuang et al, 2019; Kiesler et al, 2015; Oehlers et al, 2013; Oehlers et al, 2017), our findings raise the possibility that disruption of the visceral muscle structure could be an aspect of IBD. It has been shown that gastrointestinal motility disorders are frequently associated with IBD (Bassotti et al, 2014; Hashmi et al, 2021). Therefore, it would be interesting to investigate whether the visceral musculature is affected in IBD animal models and patients.…”
Section: Discussionmentioning
confidence: 99%